2013
DOI: 10.1007/s10916-012-9916-1
|View full text |Cite
|
Sign up to set email alerts
|

Simple Group Password-based Authenticated Key Agreements for the Integrated EPR Information System

Abstract: The security and privacy are important issues for electronic patient records (EPRs). The goal of EPRs is sharing the patients' medical histories such as the diagnosis records, reports and diagnosis image files among hospitals by the Internet. So the security issue for the integrated EPR information system is essential. That is, to ensure the information during transmission through by the Internet is secure and private. The group password-based authenticated key agreement (GPAKE) allows a group of users like do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Studies have also indicated that patients are reluctant to share their health information other than for direct clinical care (Li et al 2011). EHRs are shared among different systems and this openness raises considerable concern about patient privacy owing to the possibility of unauthorised access or misuse owing to improper security implementation . Privacy means that patients have the right to handle the disclosure of their personal information (Lee, Chang & Wang 2013). Data security means the protection of personal information against 'accidental or unlawful destruction or accidental loss, alteration, unauthorized disclosure or access' (van der Haak et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also indicated that patients are reluctant to share their health information other than for direct clinical care (Li et al 2011). EHRs are shared among different systems and this openness raises considerable concern about patient privacy owing to the possibility of unauthorised access or misuse owing to improper security implementation . Privacy means that patients have the right to handle the disclosure of their personal information (Lee, Chang & Wang 2013). Data security means the protection of personal information against 'accidental or unlawful destruction or accidental loss, alteration, unauthorized disclosure or access' (van der Haak et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first comparison concerned computations. These GAKA protocols [3,7,8,13,14] require many time-consuming modular exponential computations or scalar multiplications on elliptic curves to realize authentication and negotiate group keys. Only the proposed GAKA protocol was developed using extended chaotic map operations and did not have a heavy computational burden.…”
Section: Performance Analyses and Comparisonsmentioning
confidence: 99%
“…The protocols of Kim et al [7] and Boyd and Nieto [8] realize authentication using users' public keys. The GAKA protocols of Abdalla et al [3], Dutta and Barua [13], and Lee et al [14] as well as the proposed GAKA protocol realize authentication using users' passwords. However, in the GAKA protocols of Abdalla et al [3] and Dutta and Barua [13], all users share the same password so their protocols do not ensure users' privacy.…”
Section: Performance Analyses and Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations